Characterization of LTR-Retrotransposons on Hemileia vastatrix genome - Rocha, Rafaela Leite Prado (2017)
Brazil is the biggest producer and exporter of coffee in the world. The country, as the rest of coffee growing regions, suffers with coffee rust disease. Rust, one of the earliest coffee diseases studied scientifically, is caused by the obligate biotrophic fungus Hemileia vastatrix. This disease is the most harmful that affects coffee trees, which may cause drastic drops in productivity if not controlled. The fungus infects coffee leaves penetrating through stomata and develops powdery orange pustules on the abaxial surface. The pathogen displays high levels of genetic variability leading to appearance of new physiological races and supplanting the resistance of coffee varieties obtained in breeding programs. The mechanism that causes such variability is yet not known, since it is accepted that the fungus relies on asexual reproduction and the sexual stage has not been observed in nature. The genome of H. vastatrix has been reported as one of the largest known rust genome. A very large fraction of the published rust genomes has shown a high percentage of repetitive elements, such as transposable elements (TEs). In this sense, TEs activity is suggested as an important source for generation of variability. Thus, there is a chance that the transposable DNA elements are responsible for increasing genetic variability of H. vastatrix. Therefore, this study aimed to identify presence, frequency and location of transposable elements, as well as verify the relationship between transposable elements and the high variability found on genome of H. vastatrix. We found 6,516 gene- coding proteins and 1,109 complete LTR retrotransposons in the genome. From these gene-coding proteins, 65 were close to LTR retrotransposons. The results suggested that LTR retrotransposon generally insert itself 5,000bp from a gene-coding protein. Also, LTR retrotransposons identified insert itself on AT-rich conserved regions. Thus, the found data suggest that insertion of LTR retrotransposons in H. vastatrix genome could be targeting its integration site based on nucleotide composition. Moreover, we identified LTR retrotransposons located close to coding regions, which could be contributing with gene expression modulation and hence affecting pathogen variability.